Outcome and potentially modifiable risk factors for candidemia in critically ill burns patients: A matched cohort study. Issue 3 (18th December 2018) - Dudoignon, Emmanuel; Alanio, Alexandre; Anstey, James; Depret, François; Coutrot, Maxime; Fratani, Alexandre; Jully, Marion; Cupaciu, Alexandru; Chaussard, Maïté; Oueslati, Haikel; Ferry, Axelle; Benyamina, Mourad; et al.
Summary: Background: Patients with extensive burns are at risk of developing candidemia. Objectives: To identify potentially modifiable risk factors and outcomes of candidemia in critically ill burns patients. Patients and Methods: Retrospective matched cohort study including adult burns patients. Patients who developed candidemia were matched with burns patients with Candida spp colonisation and sepsis or septic shock without candidemia in a ratio of 1:3 (same severity scores and colonisation index). Univariate and multiple regression analyses were performed. Results: Of 130 severely burned patients with Candida spp colonisation and at least one episode of sepsis or septic shock, 14 were diagnosed with candidemia. In the candidemia group, patients had a median (IQR) total burns surface area (TBSA) of 57 (38‐68)%, SAPSII of 43 (36‐58) and ABSI of 11 (8‐13). Multiple regression analysis showed that only duration of prior antibiotic therapy was independently associated with candidemia. ICU mortality was higher in the candidemia group (71% vs 35% [ P  =   0.02]). The log‐rank test for 28‐day mortality comparing patients with candidemia treated with an empirical strategy vs a curative strategy did not reach significance ( P  =   0.056). Conclusions: Burns patients having received recent antibiotherapy have a higher risk of candidemia. Antifungal strategies did not influence outcome in this series.